2010
DOI: 10.1111/j.1553-2712.2010.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Computed Tomography Angiography of the Brain Replace Lumbar Puncture in the Evaluation of Acute‐onset Headache After a Negative Noncontrast Cranial Computed Tomography Scan?

Abstract: Objectives: The primary goal of evaluation for acute-onset headache is to exclude aneurysmal subarachnoid hemorrhage (SAH). Noncontrast cranial computed tomography (CT), followed by lumbar puncture (LP) if the CT is negative, is the current standard of care. Computed tomography angiography (CTA) of the brain has become more available and more sensitive for the detection of cerebral aneurysms. This study addresses the role of CT ⁄ CTA versus CT ⁄ LP in the diagnostic workup of acute-onset headache.Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 39 publications
0
84
0
2
Order By: Relevance
“…Thus, if a patient presents several days after ictus, a negative non-contrast CT is commonly supplemented with a lumbar puncture to evaluate for xanthochromia. Alternatively, CT angiography (CTA) has also been used to increase the detection rate of ruptured cerebral aneurysms in instances where there is a high index of clinical suspicion and a negative noncontrast CT. McCormack et al [15] reported that a negative non-contrast CT followed by a negative CT angiogram carries a post-test probability of 99.43 % of being negative for aneurysmal subarachnoid hemorrhage. The investigators argued that a lumbar puncture in this setting would carry a less than 1 % probability of detecting subarachnoid hemorrhage and that patients should be informed of the low probability when lumbar puncture is offered.…”
Section: Computed Tomography and Ct Angiographymentioning
confidence: 99%
“…Thus, if a patient presents several days after ictus, a negative non-contrast CT is commonly supplemented with a lumbar puncture to evaluate for xanthochromia. Alternatively, CT angiography (CTA) has also been used to increase the detection rate of ruptured cerebral aneurysms in instances where there is a high index of clinical suspicion and a negative noncontrast CT. McCormack et al [15] reported that a negative non-contrast CT followed by a negative CT angiogram carries a post-test probability of 99.43 % of being negative for aneurysmal subarachnoid hemorrhage. The investigators argued that a lumbar puncture in this setting would carry a less than 1 % probability of detecting subarachnoid hemorrhage and that patients should be informed of the low probability when lumbar puncture is offered.…”
Section: Computed Tomography and Ct Angiographymentioning
confidence: 99%
“…SAH from other causes tends to have a better prognosis and repeat angiography is generally unwarranted (18). A recent analysis of the utility of CTA in the workup of possible SAH determined that, if the pretest probability of SAH is # 15% (acute-onset headache, nonfocal neurologic examination), then a negative NCCT and negative CTA would correlate to a <1% chance of SAH due to AVM or aneurysm (29). These authors stated that in patients with a higher pretest probability (e.g., those with classic presentation, abnormal neurologic examination, or risk factors), a strategy incorporating NCCT, CTA, and LP may be appropriate.…”
Section: Ct/ctamentioning
confidence: 99%
“…22 A single prospective study of patients with clinical presentations suggestive of SAH has been performed directly comparing CT/CTA with CT/ LP in 106 patients. 6 Based on strict criteria, 2 patients had positive results of LP, and in both cases aneurysms were revealed by CTA and confirmed by DSA.…”
Section: Discussionmentioning
confidence: 99%